2010
DOI: 10.1017/s1355617710000792
|View full text |Cite
|
Sign up to set email alerts
|

Right hemisphere infarct patients and healthy controls: Evaluation of starting points in cancellation tasks

Abstract: Patients with visual neglect (VN) tend to start cancellation tasks from the right. This exceptional initial rightward bias is also seen in some right hemisphere (RH) stroke patients who do not meet the criteria of VN in conventional tests. The present study compared RH infarct patients’ (examined on average 4 days post-stroke) and healthy controls’ starting points (SPs) in three cancellation tasks of the Behavioural Inattention Test (BIT). Furthermore, task-specific guideline values were defined for a normal S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 22 publications
2
20
1
2
Order By: Relevance
“…Previous clinical studies (Azouvi et al, 2002(Azouvi et al, , 2006Jalas, Lindell, Brunila, Tenovuo, & Ha¨ma¨la¨inen, 2002;Mattingley, Bradshaw, Bradshaw, & Nettleton, 1994;Nurmi et al, 2010;Samuelsson, Hjelmqvist, Naver, & Blomstrand, 1996) have found that stroke patients with or without VN show pathological attention processes, including a right-to-left visual scanning strategy. In the study of Jalas et al (2002) the starting point in different cancellation tasks was designated right or left with respect to the center of the stimulus sheet.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous clinical studies (Azouvi et al, 2002(Azouvi et al, , 2006Jalas, Lindell, Brunila, Tenovuo, & Ha¨ma¨la¨inen, 2002;Mattingley, Bradshaw, Bradshaw, & Nettleton, 1994;Nurmi et al, 2010;Samuelsson, Hjelmqvist, Naver, & Blomstrand, 1996) have found that stroke patients with or without VN show pathological attention processes, including a right-to-left visual scanning strategy. In the study of Jalas et al (2002) the starting point in different cancellation tasks was designated right or left with respect to the center of the stimulus sheet.…”
Section: Introductionmentioning
confidence: 97%
“…Earlier studies (Azouvi et al, 2002;Jalas et al, 2002;Mattingley et al, 1994;Samuelsson et al, 1996) have measured rightward bias using mainly dichotomous variables (left vs right) or an ordinal scale (columns), and functional and neurological outcomes have not been systemically reported (e.g., Jalas et al, 2002;Mattingley et al, 1994). Furthermore, results have only been reported for the acute phase of stroke (e.g., Jalas et al, 2004;Nurmi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that an ipsilesional bias in orientation of attention (i.e., an initial ipsilesional orientation of attention) is a fundamental component of VSN (Azouvi et al, 2002(Azouvi et al, , 2006Gainotti, 2010;Gainotti, D'Erme, & Bartolomeo, 1991;Jalas, Lindell, Brunila, Tenovuo, & Hamalainen, 2002;Karnath, 1988;Kettunen, Nurmi, Dastidar, & Jehkonen, 2012;Kinsbourne, 1993;Mattingley, Bradshaw, Bradshaw, & Nettleton, 1994;Nurmi et al, 2010;Samuelsson, Hjelmquist, Naver, & Blomstrand, 1996;Stone et al, 1991;Webster et al, 1995). It has also been considered that impaired speed in perceptual processing represents an additional core component of the neglect phenomena .…”
mentioning
confidence: 99%
“…16 Figure 2). Compared with sham treatment, cTBS over the left PPC resulted in an improvement in LBT score between baseline and Post 2, as revealed by ANOVA analysis showing a group  time effect (F 2,18 ¼ 13.522; P < 0.001) and a group  time interaction (F 2,18 ¼ 4.050; P ¼ 0.045).…”
Section: Resultsmentioning
confidence: 99%